Quality of life and traumatic spinal cord injury: a study using international data sets - Faleiros, Fabiana (2020)
The aim of this quantitative, analytical and cross-sectional study was to assess the quality of life (QOL) of people with a traumatic spinal cord injury (SCI) and its association with the length of time of SCI. Data were collected using two validated instruments (a biological and sociodemographic questionnaire and the QOL Data Set from the International Spinal Cord Society). The sample included 81 participants, 81.5% male, with a mean age of 36±11.9 years. Satisfaction with psychological health had a higher score (7.2), despite 86.4% being dissatisfied or completely dissatisfied with overall QOL. There was no difference when comparing the SCI level to satisfaction with overall life (p=0.237). General QOL was associated with the length of time of SCI (p=0.005), suggesting that after five years of SCI, people tend to be more satisfied with their lives. This study showed that most participants with SCI are dissatisfied with their quality of life.